Supratentorial Extra-axial Ependymoma: A Rare Radiological Mimic of Cystic Meningioma - Ghazali, Fattah Rahiman; Zaidin Samsudin1, Ahmad Hadif (International Journal of Human and Health Sciences (IJHHS), 2022)
Ependymoma is commonly an intra-axial infratentorial tumour affecting paediatric age group. We report a rare case of supratentorial extra-axial ependymoma in a teenager who presented with worsening headache and mild cognitive impairment. Previously, only few of such cases have been reported in the literature. However, in the last decade, there has been increasing number of this rare entity represented as a solid-cystic mass. In this report, we discuss the radiological features as we think it is mimicking a cystic meningioma and recommend that ependymoma should be considered in the diagnosis of a solid-cystic extra-axial lesion especially when located supratentorially. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 338-341